Wanita Rawan Sosial Ekonomi Di Kecamatan Semin, Gunungkidul - Khoirudin, Rifki (Elastisitas : Jurnal Ekonomi Pembangunan, 2019)
Socio-economic is a condition that can affect a person in running his life, causing social interaction. Socioeconomic can have good and bad impacts. Good effect if the welfare is high but will have a bad impact if the welfare is low and results in social inequality, one of which is a socioeconomic vulnerable woman who has low welfare, the Socioeconomic Prone Woman (hereinafter referred to as WRSE) is a problem that needs attention, because one of the factors contributing to poverty is a socioeconomic-prone woman whose income is below average. So that low income results in social inequality. Semin Sub-district is a district which has cases of PMKS especially at the highest WRSE in Gunungkidul Regency. This study aims to analyze the independent variables include, marital status, age, and length of informal education whether it has a significant effect on women who are socio-economic vulnerable. The form of data used is cross section. Hypothesis testing is carried out logistic regression with logit analysis which is processed using the SPSS application. Determination of the number of samples in this study was determined randomly, then the number of samples was calculated using the Slovin formula of 93 respondents. The results showed that of the three independent variables, only one variable did not affect WRSE, namely age, while marital status and length of informal education significantly affected socioeconomic vulnerable women in Semin Sub-district, Gunungkidul.Keywords: WRSE, Marital Status, Age, Length of Informal Education.